The Role of Counseling Guidance in Optimizing the Effectiveness of Sport Education for Character Formation of Students - Silviah, Reni (Journal of Law, Politic and Humanities, 2022)
The literature review on the role of counseling guidance in optimizing the effectiveness of sports education for the character development of students is a scientific article aimed at analyzing whether character formation is influenced by counseling guidance and sports education. The method used is a qualitative approach with descriptive study type (literature review) to explore and analyze the relationship between counseling guidance, sports education, and character development. The results of this article are: 1) Counseling guidance plays a role in character formation, 2) Sports education plays a role in character formation. In addition to these two exogenous variables that influence the endogenous variable of character formation, there are many other factors including the quality of education, discipline, physical activity, and leadership.